ATTRACTION OF ABANG ISLAND AS A MARINE TOURISM OBJECT IN BATAM CITY RIAU ISLANDS PROVINCE - Agustina, Winda Khairunnisak; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Abang Island is one of the villages in Galang District. Abang Island is an area that has been designated as a conservation area. This study aims to determine the description of the attraction of marine tourism on Abang Island and the efforts of the local government regarding the attractiveness of marine tourism on Abang Island. This study uses a qualitative method with a descriptive approach. The subjects of this study were tourists, Department of Tourism and Culture Batam City, Village Head of Abang Island, Abang Island tourism business actors, Abang Island Tourism Awareness Group, and the local community. This research was conducted by collecting data in the form of observation, interviews, and documentation. The results of this study indicate that Abang Island has a marine tourism attraction in the form of the amazing and charming underwater beauty and uniqueness of Abang Island. On the underwater surface of Abang Island, there are rare coral reefs that are still awake and various types of marine life coupled with views of white sand beaches and good and clear sea water quality. In addition, the government's efforts in developing Abang Island marine tourism are maintaining cleanliness, supporting small home-based businesses, building homestays, increasing human resources on Abang Island, and forming Abang Island Tourism Awareness Groups. Keywords: Attraction, Marine Tourism, Abang Island